Trillo, Juan Manuel y Lois, Rubén Camilo (eds.) (2019). Paisaxes nacionais no mundo global - Agrelo Janza, Luis Martín (Documents d’Anàlisi Geogràfica, 2020)
Trillo, Juan Manuel y Lois, Rubén Camilo (eds.) (2019) Paisaxes nacionais no mundo global Santiago de Compostela: Grupo de Análise Territorial (ANTE) GI-1871, 165 p. ISBN 978-84-09-09687-9